Paramecium, a Model to Study Ciliary Beating and Ciliogenesis: Insights From Cutting-Edge Approaches - Bouhouche, K.; Valentine, M. S.; Le Borgne, P.; Lemullois, M.; Yano, J.; Lodh, S.; Nabi, A.; Tassin, A. M.; Van Houten, J. L. (Frontiers in Cell and Developmental Biology, 2022)
Cilia are ubiquitous and highly conserved extension that endow the cell with motility and sensory functions. They were present in the first eukaryotes and conserved throughout evolution (Carvalho-Santos et al, 2011). Paramecium tetraurelia has around 4000 motile cilia on its surface arranged in longitudinal rows, beating asymmetrically to ensure movement and feeding. Direction and speed of Paramecium ciliary beating is dependent, as with cilia in other models organisms, under bioelectric control by ciliary ion channels. In multiciliated cells, the cilia become physically entrained to beat in metachronal waves in protists as well as in metazoans. This ciliated organism is a model of choice for the use of multidisciplinary approaches to dissect the location, structure and function of ciliary ion channels and other proteins involved in ciliary beating. Swimming behavior also can be a read out of the role of cilia in sensory signal transduction. Cilia emanate from a basal body (BB), structurally equivalent to the centriole, anchored at the cell surface and elongate an axoneme composed of microtubule doublets, enclosed in a ciliary membrane contiguous with the plasma membrane. The connection between the BB and the axoneme constitutes the transition zone, which serves as a diffusion barrier between the intracellular space and the cilium, defining the ciliary compartment. Human pathologies affecting cilia structure or function, are called ciliopathies which are caused by gene mutations. For that reason, the molecular mechanisms and structural aspects of cilia assembly and function are actively studied using a variety of model systems, ranging from unicellular organisms to Metazoa. In this review, we will highlight the use of Paramecium as a model to decipher ciliary beating mechanisms and high resolution BB structure as well as insights in BB anchoring process. We will show that cilia study in Paramecium potentiates our understanding of cilia formation and function. In addition, we demonstrate that Paramecium could be a useful tool to validate candidate genes associated to ciliopathies.